Social Support and Stress-Related Acculturative Experiences of an English-speaking Afro-Caribbean Female Student in U.S. Higher Education - Rahming, Sophia (Journal of International Students, 2019)
This two-year qualitative single critical case study research investigated the stress-related adjustment experiences and academic progression of a female English-speaking Afro-Caribbean collegian in an American postsecondary institution through the lens of the “triple bind” phenomenon and the stress buffer hypothesis. Student development theory and research on college student outcomes have largely focused on Black students’ experiences and achievement outcomes through a homogeneous African American cultural lens. Minimal existing research has shown differences in the lived experiences and achievement outcomes between Afro-Caribbean students and domestic African American students in U.S. postsecondary education.